A Model of Surveillance Behavior Patterns of Youth in the Five Precepts Keeping Village Project at Nakhon Pathom Province - Ninkron, Paranee; Khuntiterakul, Praphan (Princess of Naradhiwas University Journal, 2021)
This research aimed to create a model of surveillance behavior patterns of youth substance use in the Five Precepts Keeping Village Project, Nakhon Pathom Province. A mixed-methods research design was conducted. The 1st phase was to investigate factors related to the use of addictive substance among 302 youths aged 15 - 21 years, and the data were analyzed by Multiple Regression. Then the qualitative method was involved in studying causes of the problem; a model of surveillance behavior patterns was developed. The qualitative data were analyzed by thematic analysis with data triangulation verification. The results found that the self-control of drug use, holistic health, perceived ability, self-efficacy in substance abuse prevention were the determinants to predict the use of addictive substance among youths in the five precepts village. Moreover, the model of surveillance behavior patterns of youth substance use consisted of 2 programs: (1) the development plan for the individual’s capabilities, consisting of plans to organize a public hearing, set up youth leader group, provide career training, provide supports in sport and health recreation activities and build awareness in media perception, and (2 the environmental adjustment plan consisting of exchange of ideas between parents or guardians, community leaders, teachers and religious leaders to discuss about prevention of drug in the community and plan to set up mind and wisdom development center based on 5-precepts concepts.